Influence of Chemical Composition on Layer Properties of Barrel Steels - Pokorny, Zdenek; Dobrocky, David; Studeny, Zbynek (Manufacturing Technology Journal, 2018)
This article deals with influence of chemical composition on depth of diffusion layers and porosity of compound layers after gas nitriding process. Experiments are focused on utilizing of gas nitriding processes for surface treatment. Gas nitriding technologies were applied to steels C 35 (sample A1), 34Cr4 (sample A2) and steel 42CrMo4 (sample A4), which were subsequently evaluated by electron microscopy, GDOES and microhardness methods. The measurements showed the influences of chemical composition of alloying elements in core of material after chemical-heat treatment process on depth of diffusion and influence of technology on development of porosity. Nevertheless, the main task was the description of the porosity development in compound layer after gas nitriding and the increasing of surface hardness and of the depth of diffusion layer according to chemical composition. Gas nitriding process was applied for increasing of surface hardness of material in depth and improving of mechanical properties. Mechanical properties of tested material were significantly increased.
Keywords: gas nitriding; microhardness; nitrided layer; porosity